Pengaruh Likuiditas, Leverage, Profitabilitas dan Ukuran Perusahaan terhadap Financial Distress: Studi Pada Perusahaan Sub Sektor Wholesale di BEI Periode - Eka Oktaviani; Ferikawita M. Sembiring (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: This study transfers to see if variables in financial risk and company size will affect financial distress condition of wholesale sub-sector companies on the IDX the 2014-2020 period. Research methodology: This research method is a quantitative that uses a descriptive and associative analysis with purposive sampling technique to acquire 9 wholesale sub-sector companies listed on the IDX for the period 2014-2020. The method of data analysis used is the data panel analysis. Results: The results showed that the variables of debt to asset ratio, debt to equity ratio, and return on asset had of effect on financial distress, while current ratio, return on equity and firm size had no effect. Simultaneously all variables affect the occurrence of financial distress. Limitation: The limitation of this study is on variable are still possible to be added or developed by other studies and also the possibility of using other financial distress measurement method. Contribution: Produce findings on factor that can affect financial distress conditions in wholesale (durable and non-durable goods) sub-sector companies listed on the IDX during the 2014-2020 period.